The dependence of the nuclear charge form factor on short range correlations and surface fluctuation effects - Massen, S. E.; Garistov, V. P.; Grypeos, M. E. (HNPS Advances in Nuclear Physics, 2020)
An investigation is carried out in order to study effects, originating from fluctuations of the nuclear surface, to the elastic charge form factor of light nuclei in which the two-body part of the short range correlation factor is also included through a Jastrow-type correlation function. It is found that if these effects are taken into account in the uncorrected (harmonic oscillator) part of such a form-factor for the 4He, l6O and 40Ca nuclei, the quality of the fitting is improved. In addition, they lead to a drastic change in the asymptotic behaviour of the point-proton form factor which now drops off for large values of the momentum transfer q quite slowly that is as const.•q^-4.